Physico-mechanical, thermal insulation and resistance characteristics of diatomite and attapulgite based geopolymer foam concrete: Effect of different curing regimes - Bodur, Burak; Bayrak, Baris; Yavuz Bayraktar, Oguzhan; Aydin, Abdulkadir Cüneyt; Kaplan, Gökhan; Çelebi̇, Oğuzhan; Öz, Ali (Elsevier BV, 2023)
This study investigated the physicomechanical, durability and microstructure characteristics of geopolymer foam concrete (GFC) with a unit weight of less than 1500 kg/m3 produced using attapulgite and diatomite. In the blends, as the main binder was used 10, 20 and 40% attapulgite instead of ground blast furnace slag (GBFS). In addition, 30, 40 and 50 kg/m3 foam were used in the blends. Three alternative curing methods were used on GFC: steam (80 °C), water (∼22 °C), and an oven (80 °C). Thermal curing regimens last 24 h at a temperature of 80 °C. The blends’ porosity ranges from 36.8 to 53.3%, while their levels of water absorption range from 32.5 to 49.4%. Unit weights of hardened GFC samples range from 475 to 1226 kg/m3. On the 28th day, after applying the steam curing to blends with a 30 kg/m3 foam dosage, the compressive strength is greater than 5 MPa. After 900 °C heat treatment (elevated temperature effect), a blend with a foam dosage of 30 kg/m3 and 40% attapulgite produced compressive strengths of greater than 4 MPa. The blends’ depths of water penetration range from 22.1 to 27.8 mm. The drying shrinkage of the blends was increased by adding more foam and attapulgite. GFC's thermal conductivity coefficient varies from 0.134 to 0.354 W/m.K. Increasing the attapulgite and foam decreased the thermal conductivity coefficient. Reaction products such as CASH and NASH gels were observed in SEM examinations. As a result, it has been determined that the most suitable results (In terms of physico-mechanical, thermal insulation and strength Properties) can be obtained if steam curing is applied in blends with 20% attapulgite and 30 kg/m3 foam dosage.